Pelaksanaan Pembebasan Bersyarat Bagi Anak Pelaku Tindak Pidana (Studi di BAPAS klas i Kota Cirebon - sanusi sanusi (Fakultas Hukum Universitas Swadaya Gunung Jati, 2015)
PELAKSANAAN PEMBEBASAN BERSYARAT BAGI ANAK PELAKU TINDAK PIDANA (Studi di BAPAS Klas I Kota Cirebon) Oleh :Sanusi & Ratu Ineke. MABSTRACTPresence of children in the surrounding environment must be considered progress, often a child to act even lead to deviations crime. Thus making the child was forced to convicted even so, the needs of children comes first. In order to assist the child to become accepted by the community needed Correctional Center to monitor the child's development. Because BAPAS have an important role in the juvenile justice process. Officers Society (PK) facilitate the task assigned to assist investigators and prosecutors in matters brat conflict with the law by creating a social study (Litmas) and play a role in the guidance program.Based.on.the.above, the authors identified the.problem, how to program and criteria Parole child criminals and how the constraints in the implementation of conditional release program in the face by Bapas. The.purpose of.this thesis to determine the.extent to.which the provisions of.the Parole program implementation.can be realized when coaching at Bapas. Method research approach used is more emphasis on the juridical aspect-empirical.The research results show that, the program and the criteria applied by the Parole Bapas Cirebon are in accordance with the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 21 Year 2013 About Conditions and Procedures for granting remission, Assimilation, Visiting Family Leave, Parole, Leave Towards free, and leave Conditional.Especially on Parole program.In Bapas there are three (3) phases of the program guidance ie, early stage, advanced stage and final stage. In the early stages of guidance and advanced stages of some procedures are not executed, and also the lack of provision of time required to report for the client. The constraints faced Bapas in terms of facilities and lack of human resources, led to the implementation of supervision becomes less than optimal. The author recommends that the Ministry of Justice and.Human.Rights pay more attention to the deficiencies found in Cirebon Bapas well as provide more detailed rules on the program guidance.Keywords: Child Crime, Parole, and Program Guidance..